Memahami Konsep Dasar Akuntansi Menggunakan Metode ”Role Play”: Studi pada Gereja Kristen Pasundan Indonesia - Joni, Joni; Tjun, Lauw Tjun; Marpaung, Elyzabet Indrawati; Setiana, Sinta; Natalia, Maria; Eddy, Endah Purnama Sari; Alamsyah, Andea; Sie, Inri Imelix; Gultom, Putriyani (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Financial management in non-profit organizations, including churches, plays a strategic role in ensuring transparency, accountability, and sustainability of services. The Pasundan Christian Church (GKP) has established the Interpretation of Financial Accounting Standards (ISAK) 335 as the primary guideline for preparing financial reports. However, initial implementation has shown significant obstacles, particularly related to limited understanding of accounting. The need for the GKP Synod administrators to provide a sound understanding of accounting concepts and practices within the synod environment prompted the implementation of community service in the form of accounting training. The objective of this activity was to provide a proper understanding of basic accounting concepts through the Role Play (RPL) method for GKP treasurers and finance secretariat staff. This Community Service (PkM) activity successfully improved understanding of basic accounting concepts through the application of the RPL method. These findings demonstrate that the RPL method is effective in improving accounting understanding, especially for participants with limited prior knowledge. The success of this training supports the GKP's need to implement a digital accounting system in accordance with ISAK 335, as improved accounting understanding among treasurers will simplify the recording process and produce more accurate and credible financial reports.